MiR‐218 contributes to drug resistance in multiple myeloma via targeting LRRC28. Issue 3 (8th January 2021) - Chen, Haifei; Cao, Weiling; Chen, Jiao; Liu, Danbo; Zhou, Lingyun; Du, Fang; Zhu, Feiqi
Abstract: Multiple myeloma (MM) is a malignant neoplasm featured by obvious drug resistance and poor prognosis. MicroRNAs (miRNAs) are a class of small noncoding RNAs with crucial roles in many biological processes including cancer initiation and progression. The current study aims to investigate the pathogenic role and molecular mechanism of miRNAs in MM drug resistance. In the present study, The expression profile of miRNAs in MM samples was analyzed by microarray and real‐time polymerase chain reaction. Protein expressions were detected by Western blot analysis. Cell apoptosis was detected by the Annexin V staining assay. The interaction between miRNA and the targeting mRNA was assessed using Dual luciferase reporter assay. Herein, we show that expression profile of miRNAs is deregulated in MM. miR‐218, one of the most aberrational miRNAs in MM, is significantly decreased in MM cells compared to peripheral blood mononuclear cell (PBMC). Genetic manipulation reveals miR‐218 control the response of MM cells to anticancer drug bortezomib (BTZ). Overexpression of miR‐218 causes a significant aberrant genes expression including leucine rich repeat containing 28 (LRRC28). Mechanistic study shows that miR‐218 control the drug response through mediating the expression of LRRC28 in MM cells. Overexpression of LRRC28 significantly reserves miR‐218‐mediated cell response to BTZ. Taken together, miR‐218 is decreased in MM that contributes to BTZ resistance via targeting LRRC28, which might be used as a novel therapeutic target for multiple myeloma.